THE EXPERIMENTAL PHYSICS PROBLEMS AT THE TECHNICAL UNIVERSITY - Podlasov, Serhii; Sverdlichenko, Dmitry; Matviichuk, Oleksii (Physical and Mathematical Education, 2023)
Formulation of the problem. The training of engineers at a technical university involves not only mastering students’ theoretical knowledge, but also acquiring skills of their practical application, since the ability and willingness of an engineer, if necessary, to solve research problems, is one of the requirements for the qualification of a specialist in the documents of the International Engineering alliance and the European Federation of Engineering Associations. Significant opportunities for this, especially in the conditions of distance learning, have experimental tasks that can be offered to students for independent solving at home using available tools. Materials and methods. The research is based on the analysis of physics course programs for the bachelors of engineering specialties, a review of literary sources devoted to the researched and problems from traditional physics problems books that can be reformulated into experimental ones. The data needed to solve the problem must be found from an experiment that students conduct at home in distance learning conditions. The needed equipment must be available or easily manufactured, as well as free distributed software for computer and smartphone. Results. The analysis of training programs and a review of literary sources allowed to select from the sections "Mechanics", "Molecular Physics", "Electric Current", "Mechanical Oscillations" of standard collections of physics problems that can be used as experimental and which students are able to solve at home. The ability to set up the necessary experiment, to a certain extent, can be considered an art that not all students possess. This necessitates to develop the guidelines for conducting experiments related to the experimental problem conditions. Conclusions. The examples of experimental problems demonstrated the possibility of their application in distance learning. Solving such problems should contribute to the development of students’ experimental skills and their ability to apply theoretical knowledge to solve practical problems.